2019
DOI: 10.3389/fnana.2018.00118
|View full text |Cite
|
Sign up to set email alerts
|

The Organization and Connections of Second Somatosensory Cortex in the Agouti

Abstract: In order to understand how the mammalian sensory cortex has been structured during evolution, it is necessary to compare data from different species across distinct mammalian lineages. Here, we investigated the organization of the secondary somatosensory area (S2) in the agouti (Dasyprocta aguti), a medium-sized Amazonian rodent, using microelectrode mapping techniques and neurotracer injections. The topographic map obtained from multiunit electrophysiological recordings were correlated with both cytochrome ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 85 publications
3
13
0
Order By: Relevance
“…In agreement with reported electrophysiological data 22 , the overall body map in the mouse S2 lies laterally from S1 with a mirrored topographic organization, global features that seem to be shared with other rodent species 6,45,46 . Stimulation of up to 24 individual whiskers in 9 mice revealed that although the cortical territory devoted to whiskers in S2 is about an order of magnitude smaller than in S1, it is characterized by a clear somatotopic organization with a discernable topographic arrangement of individual whiskers.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with reported electrophysiological data 22 , the overall body map in the mouse S2 lies laterally from S1 with a mirrored topographic organization, global features that seem to be shared with other rodent species 6,45,46 . Stimulation of up to 24 individual whiskers in 9 mice revealed that although the cortical territory devoted to whiskers in S2 is about an order of magnitude smaller than in S1, it is characterized by a clear somatotopic organization with a discernable topographic arrangement of individual whiskers.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the squirrel neocortex volume 80 and the ratio 79 sourced from previous literature. Neocortex volume of the agouti was calculated by multiplying the cortical flat-mount area 81 with cortical thickness. 21 The agouti V1/Neocortex ratio was measured from a published cortical flat-mount.…”
Section: Calculation Of the V1/neocortex Ratio And Volumesmentioning
confidence: 99%
“…21 The agouti V1/Neocortex ratio was measured from a published cortical flat-mount. 81 The capybara neocortex volume was taken from a study by Campos and Welker 82 and the ratio was measured from a schematic diagram found in the same study. Note that the diagram was not of a flat-mount, but more akin to the dorsal view and does not take into account the gyrification found in the capybara cortex.…”
Section: Calculation Of the V1/neocortex Ratio And Volumesmentioning
confidence: 99%
“…These results can be reconciled with the “midline rule”, according to which callosal connections preferentially link “midline” sensory representations ( Berlucchi et al, 1967 ; Hubel and Wiesel, 1967 ; see also Section 5.2 ), if one only considers that skilled bimanual actions, such as object manipulations, mostly occur thanks to the simultaneous use of the thumb, index and middle fingers of each hand under foveal control and generally close to the body midline. The convergence of callosal axons at the SI/SII borders observed in rodents ( Fenlon et al, 2017 ; Suárez et al, 2014b ; Zhou et al, 2021 ) is related to the underlying somatotopy ( Olavarria and Van Sluyters, 1995 ), and conforms to the “midline rule”: the somatosensory maps in SI and SII are very similar in rat, mouse, hamster, and in agouti, evidencing that body regions close to the midline (head, upper vibrissae, trunk and proximal limbs) are represented in the lateralmost region of SI and in the bordering medialmost region of SII, in a mirror-like fashion ( Krubitzer et al, 2011 ; Santiago et al, 2019 ). In both somatosensory and visual areas of mice, bilateral correlations, as measured with calcium imaging tend to be strongest close to the midline representations ( Shimaoka et al, 2019 ).…”
Section: Functional Properties Of Callosal Projecting Neuronsmentioning
confidence: 54%